One-pot construction of Cu and O co-doped porous g-C3N4 with enhanced photocatalytic performance towards the degradation of levofloxacin. Issue 36 (2nd July 2019) - Li, Feng; Zhu, Peng; Wang, Songmei; Xu, Xiuquan; Zhou, Zijun; Wu, Chundu
Abstract : Cu and O co-doped porous g-C3 N4 with outstanding photocatalytic degradation of levofloxacin performance was synthesized by a one-pot thermal polymerization approach. Abstract : Low visible light response and rapid recombination of photogeneration charge carriers have always been the main factors limiting the advanced application of g-C3 N4 (CN). Element doping has been confirmed to be an efficient method to improve the photocatalytic performance of CN. Here, a series of Cu and O co-doped porous g-C3 N4 (Cu/O-PCN) nanomaterials were successfully fabricated by a facile one-pot thermal polymerization approach for the first time. Compared to pure CN, the resulting Cu/O-PCN exhibited remarkably enhanced visible-light-driven photocatalytic activity towards levofloxacin (LEVO) degradation. The optimized sample of 0.5% Cu doped (Cu/O-PCN-3) presented the highest degradation rate constant of 0.0676 min −1, which was about 6.2 times higher than that of CN. Furthermore, a substantial decrease in the residual toxicity against E. coli was observed after photocatalytic degradation treatment. The superior photocatalytic performance of Cu/O-PCN was mainly attributed to the synergistic advantages of stronger visible light response, larger specific surface area, and the more effective separation and transfer of photogenerated charge carriers. Moreover, according to the trapping experiments, ·O2 − and h + were the major oxygen active species in the photocatalytic degradation process. Finally, the possible enhanced photocatalytic mechanism over Cu/O-PCN was proposed.